Personality and the education-health gradient: A note on "Understanding differences in health behaviors by education" - Gabriella Conti; Christopher Hansman (University of Essex, Institute for Social and Economic Research (ISER), 2012)
We test the robustness of the results of Cutler and Lleras-Muney (2010) on the role of personality in explaining the education-health gradient by using alternative measures of child personality available in the National Child Development Study. We show that, alternatively to the authors conclusions, personality contributes to the education-health gradient to an extent nearly as large as that of cognition.
Keywords: I12; I21; 330; health; education; cognitive ability; personality